“Efecto antibacteriano del extracto etanólico de Solanum tuberosum (chuño negro) frente a Streptococcus mutans, 2019” - Gamboa Mendoza, Lener Albert (2020)
The purpose of this experimental study was to determinate the in vitro antibacterial effect of the ethanolic extract of Solanum tuberosum (lyophilized potato: black chuño) against strains of Streptococcus mutans. The susceptibility test was performed, using the well diffusion method tested on the concentrations of 25%, 50% and 75% of Solanum tuberosum ethanolic extract. All concentrations showed inhibition halos and the sizes increased directly proportional to the concentrations used.To find the Minimum Inhibitory Concentration, the method of dilution in tubes was used, testing the same concentrations and the respective control; of each culture was plated with Mueller Hinton-Blood Agar to determine the Colony Forming Units (CFU's).The results showed that the concentration of 75% of the ethanolic extract of Solanum tuberosum was very sensitive, showing the highest average inhibition halo (16 mm) and the minimum inhibitory concentration was effective in the three concentrations, as it did not present colony-forming units in the different repetitions of the analyzed sample, of these concentrations the numerically lower was 25%. Finally, it is concluded that the ethanolic extract of Solanum tuberosum (black chuño) has antibacterial activity in vitro on the growth of Streptococcus mutans strains